Autoimmune heparin‐induced thrombocytopenia and venous limb gangrene after aortic dissection repair: in vitro and in vivo effects of intravenous immunoglobulin. Issue 6 (23rd March 2019) - Arcinas, Liane A.; Manji, Rizwan A.; Hrymak, Carmen; Dao, Vi; Sheppard, Jo‐Ann I.; Warkentin, Theodore E.
Abstract : BACKGROUND: Heparin‐induced thrombocytopenia (HIT) is a prothrombotic disorder characterized by heparin‐dependent antibodies that activate platelets (PLTs) via PLT FcγIIa receptors. "Autoimmune" HIT (aHIT) indicates a HIT subset where thrombocytopenia progresses or persists despite stopping heparin; aHIT sera activate PLTs strongly even in the absence of heparin (heparin‐independent PLT‐activating properties). Affected patients are at risk of severe complications, including dual macro‐ and microvascular thrombosis leading to venous limb gangrene. High‐dose intravenous immunoglobulin (IVIG) offers an approach to interrupt heparin‐independent PLT‐activating effects of aHIT antibodies. CASE REPORT: A 78‐year‐old male who underwent cardiopulmonary bypass for aortic dissection developed aHIT, disseminated intravascular coagulation, and deep vein thrombosis; progression to venous limb gangrene occurred during partial thromboplastin time (PTT)‐adjusted bivalirudin infusion (underdosing from "PTT confounding"). Thrombocytopenia recovered with high‐dose IVIG, although the PLT count increase began only after the third dose of a 5‐day IVIG regimen (0.4 g/kg/day × 5 days). We reviewed case reports and case series of IVIG for treating HIT, focusing on various IVIG dosing regimens used. RESULTS: Patient serum–induced PLT activation was inhibited in vitro by IVIG in a dose‐dependent fashion; inhibition of PLT activation by IVIG was much more marked in the absence of heparin versus the presence of heparin (0.2 U/mL). Our literature review indicated 1 g/kg × 2 IVIG dosing as most common for treating HIT, usually associated with rapid PLT count recovery. CONCLUSION: Our clinical and laboratory observations support dose‐dependent efficacy of IVIG for decreasing PLT activation and thus correcting thrombocytopenia in aHIT. Our case experience and literature review suggests dosing of 1 g/kg IVIG × 2 for patients with severe aHIT.